2017
DOI: 10.3892/etm.2017.5468
|View full text |Cite
|
Sign up to set email alerts
|

HIPK2 inhibits cell metastasis and improves chemosensitivity in esophageal squamous cell carcinoma

Abstract: Abstract. Esophageal squamous cell carcinoma (ESCC) is one of the most aggressive and lethal malignancies worldwide. At present, the underlying mechanisms of ESCC development and progression are poorly understood. Previous studies have demonstrated that homeodomain-interacting protein kinase-2 (HIPK2) serves an important role in cancer biology, particularly in proliferation and metastasis. However, the role of HIPK2 in ESCC cells remains unclear. In the current study, the expression of HIPK2 in ESCC specimens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…HIPK2 can be activated by several forms of genotoxic damage, such as UV radiation, ionizing radiation or antitumour drugs like cisplatin, leading to expression of proapoptotic genes. [29][30][31] Therefore, decreased HIPK2 expression in cancer might play certain roles in resistance to chemotherapy and radiotherapy. Further investigations to demonstrate the role of decreased HIPK2 in pancreatic cancer chemotherapy and radiotherapy resistance are needed.…”
Section: Discussionmentioning
confidence: 99%
“…HIPK2 can be activated by several forms of genotoxic damage, such as UV radiation, ionizing radiation or antitumour drugs like cisplatin, leading to expression of proapoptotic genes. [29][30][31] Therefore, decreased HIPK2 expression in cancer might play certain roles in resistance to chemotherapy and radiotherapy. Further investigations to demonstrate the role of decreased HIPK2 in pancreatic cancer chemotherapy and radiotherapy resistance are needed.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK shows an overall mutation rate of 2.1–3% (for the two isoforms of the catalytic subunit, respectively), ATM of 6%, DYRK2 of 2.7%, HIPK2 of 2.9%, p38α of 1.4%, and PKCδ of 1.7% (assessed via http://cbioportal.org). Reduced expression of the p53 Ser46 kinases in human tumors has been reported for four of the kinases: ATM in hormone‐negative breast cancer and non‐ small cell lung cancer; DYRK2 in colorectal cancer, hepatocellular carcinoma, and breast cancer; HIPK2 in oesophageal squamous cell carcinoma; and PKCδ in colon cancer . However, since the function of kinases depends on their specific activity and a number of Ser46 kinases, including DYRK2, HIPK2, PKCδ, and p38α, are regulated by their subcellular localization, it will be a complex task to determine their potential deregulation in cancer.…”
Section: Are P53 Ser46 Kinases Deregulated In Human Cancers?mentioning
confidence: 99%
“…These results suggested an effective function of HIPK2 deficiency in promoting tumor metastasis. Although previous studies have confirmed that suppressing HIPK2 mediates tumor invasion and metastasis in several malignancies, 15,31‐33 the mechanisms are not well defined. To our knowledge, only two signaling pathways involved in HIPK2 that oppose tumor invasion have been reported, including suppressing β4 integrin transcription 43 and promoting β‐catenin nuclear localization 15 .…”
Section: Discussionmentioning
confidence: 95%
“…29,30 Recently, emerging lines of evidence has suggested that HIPK2 might have other functions that oppose the epithelial-mesenchymal transition (EMT) process, and thus HIPK2 might inhibit tumor invasion and metastasis. 15,17,[31][32][33] However, the mechanisms involved in HIPK2-mediated tumor invasion and metastasis have not been fully elucidated, and the signaling pathways vary in different cancer types. For example, HIPK2 knockdown could induce Wnt signaling activation and β-catenin nuclear localization, and thus promote EMT and subsequent cell invasion in bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation